2023
DOI: 10.1039/d2cp05186a
|View full text |Cite
|
Sign up to set email alerts
|

Why does thionating a carbonyl molecule make it a better electron acceptor?

Abstract: The past decade has witnessed a surge of biomedical and materials applications of thiocarbonyl molecules (R2C=S), such as in photodynamic theory, organic field-effect transistors, and rechargeable batteries. The success of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…M4 with a thioester group shows higher reactivity and is more susceptible to attack by DBU-activated BnOH, which is ascribed to the weak resonance between the sulfur 3p orbital and the carbonyl π-orbital (3p−π conjugate). 59 DFT calculations also indicated that the active speciespromoting chain propagation was somewhat different in the O-to-S Substitution Effects on Thermal and Mechanical Properties. To understand the O-to-S substitution effect on the thermal properties of poly(ether-alt-ester), poly(M1), poly(M2), poly(M3), and poly(M4) were further characterized by thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…M4 with a thioester group shows higher reactivity and is more susceptible to attack by DBU-activated BnOH, which is ascribed to the weak resonance between the sulfur 3p orbital and the carbonyl π-orbital (3p−π conjugate). 59 DFT calculations also indicated that the active speciespromoting chain propagation was somewhat different in the O-to-S Substitution Effects on Thermal and Mechanical Properties. To understand the O-to-S substitution effect on the thermal properties of poly(ether-alt-ester), poly(M1), poly(M2), poly(M3), and poly(M4) were further characterized by thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Attack of M2 and M4 by DBU-activated BnOH afforded tetrahedral intermediates Int1 and Int1′ via TS1 and TS1′ , with a Gibbs free energy barrier Δ G barrier = 20.0 and 17.9 kcal/mol, respectively. M4 with a thioester group shows higher reactivity and is more susceptible to attack by DBU-activated BnOH, which is ascribed to the weak resonance between the sulfur 3p orbital and the carbonyl π-orbital (3p–π conjugate) . Subsequent cleavage of the C–O bond in Int2 and the C–S bond in Int2′ yielded Int3 and Int3′ with Δ G barrier = 14.3 and 5.7 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…In computational studies of the reaction of acetone with a simple model for LR (Ar = Ph in place of 4-MeOC 6 H 4 ), Merino established a mechanism involving splitting of the reagent to form the encounter pair B (Scheme ). The encounter pair reacts with acetone to form an adduct directly analogous to structure C in the present system employing the ortho -nitrophenyl substrate 1 in place of acetone. Subsequent steps for acetone lead to formation of thioacetone and [PhPOS] 3 .…”
Section: Resultsmentioning
confidence: 99%
“… The encounter pair reacts with acetone to form an adduct directly analogous to structure C in the present system employing the ortho -nitrophenyl substrate 1 in place of acetone. Subsequent steps for acetone lead to formation of thioacetone and [PhPOS] 3 . The present reaction proceeds in a similar manner too, via transition states TS-C/D and TS-E/F , but with an additional feature related to a change in conformation of the substrate via TS-D/E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation